Prevalence of stress and anxiety among university students during COVID-19 pandemic - Hafsah Arshad, Kinza Anwar, Hafsah Gul Khattak, Namra Batool, Bibi Farhat, Ayesha Sana, Syed Shumaim Ali, Asad Ejaz, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the level of stress and anxiety in university students during COVID-19 pandemic Methodology: A web based cross sectional survey was conducted from November 2020 to January 2021. Undergraduate students of either gender, aged 18-25 years, were included in the study. Sample size was calculated by using open Epitools online calculator and raised through non-probability snowball sampling technique. E-questionnaire was designed by using Google Form. Informed written consent was attached to e-survey. Semi structured questionnaire was used to take demographic data, for stress and anxiety; PSS-10 and GAD-7 were used. Data was analyzed by SPSS 26. Results: Out of 656 responses, 97(14.8%) were males and 559 (85.2%) were females. Most students reported moderate to high level of stress 603(91.92%) and anxiety 571(87.04%) .Higher prevalence of perceived stress and anxiety was found in age group of 20-23 years and associated with various factors including living with family, daily internet use of >8hrs, and not involved in any physical activity. Regarding Coorelation of anxiety with with GPA was (r=0.105, p=0.007) and physical exercise was (r=0.107, p=0.005). However coorelation of stress with GPA was (r=0.115, p=0.003) and physical exercise was (r=0.085, p=0.030). Conclusion: Majority participants showed moderate to severe level of stress and anxiety, which was more in females. Various factors including age group of 21-23 years, living with family, screen time> 8 hours and lack of physical activity were more prevalent among university students during the Covid-19 pandemic. Keywords: Anxiety, Covid-19, Stress, Physical Inactivity